Optimization Studies on TFC Membrane for Membrane Gas Absorption (MGA) Application - Sunarti, Abd Rahman; A. L., Ahmad (IOP Publishing, 2013)
A thin film composite (TFC) membrane has been developed by coating polydimethylsiloxane (PDMS) and glutaraldehyde (GH) on a surface porous polyvinylideneflouride (PVDF) membrane for membrane gas absorption (MGA) application. The optimum conditions for dip coating method were determined using response surface methodology (RSM). A central composite design (CCD) was used to investigate the effects of two independent factors, which PDMS concentrations (wt%) and dipping time (s) of GH on the four specific responses which are CO2 and N2 permeances, selectivity and contact angle (CA) value. The optimum conditions for PDMS concentration and GH dipping time are 10 wt% and 19 s, respectively where 354 GPU for CO2 permeance, 66 GPU for N2 permeance, 5.4 of selectivity and 132o of CA value were obtained. Through atomic force microscopy (AFM) analysis, the result shown the root mean square roughness (Rms) of the TFC membrane was 381 nm and it was double from untreated membrane Rms value. Therefore, the roughness of the surface membrane contributed to the performance of the separation in the process flow such as in MGA application. By coating PDMS, hydrophobicity of the surface membrane was improved as well.